Sub-Binomial Light - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review Letters)

Probing Single-Charge Fluctuations at aGaAs/AlAsInterface Using Laser Spectroscopy on a Nearby InGaAs Quantum Dot - Houel, J.; Kuhlmann, A. V.; Greuter, L.; Xue, F.; Poggio, M.; Gerardot, B. D.; Dalgarno, P. A.; Badolato, A.; Petroff, P. M.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; et al. (Physical Review Letters)

Intrinsic Spin Fluctuations Reveal the Dynamical Response Function of Holes Coupled to Nuclear Spin Baths in (In,Ga)As Quantum Dots - Li, Yan; Sinitsyn, N.; Smith, D. L.; Reuter, Dirk; Wieck, A. D.; Yakovlev, D. R.; Bayer, M.; Crooker, S. A. (Physical Review Letters)

Atomistic Picture of Charge Density Wave Formation at Surfaces - Wall, Simone; Krenzer, Boris; Wippermann, Stefan; Sanna, Simone; Klasing, Friedrich; Hanisch-Blicharski, Anja; Kammler, Martin; Schmidt, Wolf Gero; Horn-von Hoegen, Michael (Physical Review Letters)

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Towards the Origin of the Nonlinear Response in Hybrid Plasmonic Systems - Utikal, Tobias; Zentgraf, Thomas; Paul, Thomas; Rockstuhl, Carsten; Lederer, Falk; Lippitz, Markus; Giessen, Harald (Physical Review Letters)

Dynamic Nuclear Spin Resonance inn-GaAs - Chen, Y. S.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Physical Review Letters)

Optical Control of Coherent Interactions between Electron Spins in InGaAs Quantum Dots - Spatzek, S.; Greilich, A.; Economou, Sophia E.; Varwig, S.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review Letters)

Electrically Detected Electron-Spin-Echo Envelope Modulation: A Highly Sensitive Technique for Resolving Complex Interface Structures - Hoehne, Felix; Lu, Jinming; Stegner, Andre R.; Stutzmann, Martin; Brandt, Martin S.; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Letters)

Photon Propagation in a Discrete Fiber Network: An Interplay of Coherence and Losses - Regensburger, Alois; Bersch, Christoph; Hinrichs, Benjamin; Onishchukov, Georgy; Schreiber, Andreas; Silberhorn, Christine; Peschel, Ulf (Physical Review Letters)
Keywords: General Physics and Astronomy